The Implementation of the Village Fund Program in Pangkalseang Village, North Balantak District, During the 2022–2024 Period - Lia Aulia Dako; Ririn Apriana M Nur; Nurlila Malota (Universitas Muhammadiyah Palu, 2026)
The purpose of this qualitative research is to analyze the Implementation Of The Village Fund Program In Pangkalaseang Village North Balantak Disttrict 2022- 2024 Period. This research was conducted in Pangkalaseang Village. The type of data used in this study is primary data obtained from direct interviews with informants to ask directly about the problem under study. Data collection was carried out through observation, interviews, documentation, and literature review. In this study, the data sources used for data collection included primary and secondary data. The research instrument employed a descriptive method. Based on the results of the study regarding the Impementation Of The Village Fund Program In Pangkalaseang Village North Balantak District For The 2022-2024 Period, the implementation, monitoring, and accountability, has been effective and well-run, and is being impelemented in accordance with Government Regulation No. 7 of 2023.